Perbedayaan Masyarakat Berbasis Sustainable Development Goals (SDGS) di Desa Srimukti - Alya Syafikah Rani; Elia rossa; Dara Dinanti; Fitri Sabiyla Yassarah; Khofidah Pujilestari; Muhammad Maulana Hafizh; Puthree Maria Situmorang; Radina Amalia Maharani; Yuyun Yuyun (Universitas Maritim AMNI Semarang, 2024)
Real Work Lectures (KKN) is a learning process for students at Bayankara University, Jakarta Raya. This KKN activity is carried out as part of community service and aims to gain new learning experiences that expand knowledge, skills and awareness in social life. The presence of students fosters motivation and innovation in society, this is in line with the role of universities as innovators. Students are committed to helping local communities overcome the challenges they face in the economic, educational, social, infrastructure and environmental fields. Students participate in village development efforts by developing the potential of village human resources and learning and providing information that is useful for village development. The location of this KKN was identified in the RT. 004/RW. 006, Srimukti Village, North Tambun District, Bekasi Regency, West Java. We chose this location because we wanted to increase public awareness about maintaining environmental cleanliness which is reflected in a number of waste points. We also want them to be active in creative activities that they can do at home.